THEORETICAL ESTIMATES OF EQUILIBRIUM FE-ISOTOPE FRACTIONATIONS FROM VIBRATIONAL SPECTROSCOPY - Schauble E.A.; Rossman G.R.; Taylor Jr H.P. (My University, 2001)
The magnitude and direction of equilibrium iron-isotope (54Fe–56Fe) fractionations among simple iron-bearing complexes and α-Fe metal are calculated using a combination of force-field modeling and existing infrared, Raman, and inelastic neutron scattering measurements of vibrational frequencies. Fractionations of up to several per mil are predicted between complexes in which iron is bonded to different ligands (i.e. 4 per mil for [Fe(H2O)6]3+ vs. [FeCl4]− at 25°C). Similar fractionations are predicted between the different oxidation states of iron. The heavy iron isotopes will be concentrated in complexes with high-frequency metal-ligand stretching vibrations, which means that 56Fe/54Fe will be higher in complexes with strongly bonding ligands such as CN− and H2O relative to complexes with weakly bonding ligands like Cl− and Br−. 56Fe/54Fe will also usually be higher in Fe(III) compounds than in Fe(II)-bearing species; the Fe(II) and Fe(III) hexacyano complexes are exceptions to this rule of thumb. Heavy iron isotopes will be concentrated in sites of 4-fold coordination relative to 6-fold coordination. Model results for a ferrous hexacyanide complex, [Fe(CN)6]4−, are in agreement with predictions based on Mössbauer spectra (Polyakov, 1997), suggesting that both approaches give reasonable estimates of iron-isotope partitioning behavior.